Assessing the Potential Impacts of Reducing Philippine Corporate Income Tax and Reforming Sectoral Incentives on Poverty and Employment - Cororaton, Caesar (Animo Repository, 2020)
The Philippines needs to re-align its corporate income tax rates to its neighboring ASEAN countries to be competitive. Thus, the reduction in the corporate income tax rate, which is 30% at present to 20% in 2029 under the tax reform, is critical. However, because corporate income tax is a major source of government revenue, corporate incentives have to be reduced as well to finance/compensate for the reduction in the corporate tax. Also, to realize the full economic benefit of the reform, the government has to ensure that the resulting higher corporate income is reinvested back to the economy.